ANALISIS PERMAINAN LEGO DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA DINI - Inah Hayati; Komala Komala (IKIP Siliwangi, 2020)
Cognitive is one of the competencies that must be possessed and developed by early childhood. The most important part of cognitive is logical thinking, based on the results of data analysis of previous studies conducted by Sri, Nuzul, and Erlita (2017) and Kartini and Indria (2018) show the situation of the level that is still low in terms of logical thinking ability. This certainly needs to get a good stimulus, one of which is the method of using lego games as an effort in the development of cognitive abilities related to logical thinking in children. The purpose of this article is to find out the lego game in developing children's logical thinking abilities. The method used is the study of literature as a first step in preparing a research framework for obtaining secondary data in the field. The data collection technique is the documentation method based on the published papers and research results. Data analysis using bibliographic annotations (annotated bibliography). The sample in this study was a study entitled